PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN LEBAK - Indah Lestari; Ega Suhada (The Asia Pacific Journal Of Management Studies, 2020)
Government performance can be seen from the performance of employees or government officials. Competence is one of the main abilities that every employee must have. Motivation becomes a driving force for employees to carry out an activity in order to get the best results. The problems in this study are: The management of archives which is considered not optimal and not in accordance with the mechanism, the low ability of employees to complete work or tasks that are not rated maximally, the level of employee discipline is still low because if an employee is motivated he will come on time. This study aims to determine how much influence competence and motivation have on employee performance at the Community and Village Empowerment Service of Lebak Regency. This research method used is quantitative. The population is 40 people consisting of Civil Servants and Non Civil Servants. The sampling technique used was Boring Sample sampling. The results of the study state that competence has a positive and significant influence between the competency variable on employee performance, with a value (X1) tcount> ttable (5.091> 1.687). While motivation has tcount> ttable 3,616 ˃ 1,687) then H2 is accepted, it means that motivation has a significant effect on employee performance. And the F test shows that Fcount> F table (42.703> 3.25), it can be concluded that competence and motivation simultaneously influence employee performance. The conclusion is that there is an influence between competence, work motivation on employee performance in the PMD Kab. Lebak. Suggestions from research: the competence of each employee must be more capable, and motivation is another thing that must be considered by superiors, the quality of employee performance must be improved and leadership must be firm.